1996
DOI: 10.1044/1058-0360.0501.44
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Anxiety, Somatic Complaints, and Voice Use in Women With Vocal Nodules

Abstract: Psychosocial factors long have been associated with the development of hyperfunctional voice disorders such as vocal nodules. However, experimental evidence concerning the role of these factors in the etiology of vocal nodules specifically is sparse. The present study represents a preliminary examination of some psychosocial factors for 3 groups of adult female subjects: 27 with vocal nodules, 17 with hyperfunctionally related voice disorders other than nodules (pathological control), and 33 with no history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 21 publications
1
33
0
2
Order By: Relevance
“…37 The SRRS form was used here because it is a commonly used measure of general stress related to illness or maladaptive behavior. 20,36 Moreover, it does not place high demands on the interpretation by subjects and the time to complete it.…”
Section: Self-rating Scale Of Stress (Srrs)mentioning
confidence: 98%
See 1 more Smart Citation
“…37 The SRRS form was used here because it is a commonly used measure of general stress related to illness or maladaptive behavior. 20,36 Moreover, it does not place high demands on the interpretation by subjects and the time to complete it.…”
Section: Self-rating Scale Of Stress (Srrs)mentioning
confidence: 98%
“…In fact, fundamental frequency (Fo) is one of the most reported acoustic parameters in voice research, 1-3 mainly because it is the most reported acoustic cue for intonation 3 and because there is a need to develop "objective" outcomes for dysphonia. 1,3 A huge body of research is devoted to normative data for Fo, which shows variability associated with age and gender, [1][2][3][4][5][6][7][8][9] various speech tasks (sustained vowels, reading, conversation, singing, counting), 1-3, 6,10 different languages, 1,2,11,12 smoking habits, [13][14][15][16][17] stress, [18][19][20] dysphonia, 10,[21][22][23][24][25][26] and different data gathering and analysis systems (eg, acoustic and electroglottographic), 1,6,12,22,23,26 and reports different Fo measures (eg, mean, mode, range). 1,2,4,27 Nevertheless, data are still scarce (specifically for speakers of Portuguese).…”
Section: Introductionmentioning
confidence: 99%
“…Tension in the neck and back may affects the function and balance of the voice production. Research regarding the etiology of MTD strongly supports the association between stress and muscle tension (Altman, Atkinson & Lazarus 2005;Baker, 2008;Dietrich et al, 2008;Dietrich & Verdolini Abbott 2012;Dietrich & Verdolini Abbott, 2014;Goldman, Hargrave, Hillman, Holmberg & Gress, 1996;Helou et al, 2013;Helou, 2014). The effect of acute stress on muscle tension in the larynx has been studied by Dietrich and Verdolini Abbott (2012;2014).…”
Section: Associations Between Cortisol and Voice Symptomsmentioning
confidence: 99%
“…These nodules are the result of the traumatic and constant collision of the vocal folds, caused by the overcontraction of the laryngeal intrinsic muscles (Martins et al, 2010). Individuals with vocal fold nodules constitute a large part of the client population at voice clinics and their incidence appears to be related to occupations involving high voice use, excessive work hours and time spent in the occupation (Fritzell, 1996;Goldman, Hargrave, Hillman, Holmberg, & Gress, 1996;Martins et al, 2010).…”
Section: Chapter One 1 Introductionmentioning
confidence: 99%
“…The voice disorder associated with vocal fold nodules is commonly classified as a functional voice disorder, and the role of psychological precursors and predisposing personality factors is well recognised (Boone & McFarlane, 1988;Stemple, 1993). A range of personality (e.g., socially dominant, aggressive and impulsive), psychosocial factors (e.g., psychological stress, anxiety, and voice use) and somatic status (e.g., trouble sleeping, headache, and heartburns), have been deemed to be associated with vocal fold nodules (Goldman et al, 1996;Karkos & McCormick, 2009;Roy, Bless, & Heisey, 2000). Nodules are also frequently observed in individuals with velopharyngeal dysfunction and hearing loss; those who consistently use glottal stop substitutions; and children with attention deficit hyperactivity disorder (D'Alatri et al, 2015;Verdolini, Rosen, & Branski, 2006).…”
Section: Chapter One 1 Introductionmentioning
confidence: 99%